Prawo inspirowane życiem - nowy czeski Kodeks cywilny : (regulacja prawa spadkowego) - Kocowska-Siekierka, Elżbieta (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The paper aims at investigating how the Czech Republic (member of the European Union) deals with the problem of recodification of the Civil Law after political system transformation. The paper presents changes in Inheritance Law that strengthening testamentary freedom and modify the purview of family protection
Keywords: prawo spadkowe; Czechy; kodeks cywilny